Determinants of internationalization: differences between service and manufacturing SMEs - Anna Lejpras (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper empirically investigates the antecedents of internationalization of SMEs, focusing on differences between the manufacturing and service sectors. Specifically, employing a bivariate probit model based on survey data of approximately 3,900 East German firms, I analyze which firm-related and external factors affect a firm's decision to export and/or relocate production or other operations abroad. Generally, I find that SMEs from the manufacturing sector do more exporting than service firms. The results reveal that size, having main competitors located abroad, and introducing a novel product all are significantly positively related to the internationalization of SMEs regardless of industry affiliation. However, manufacturing firms in the high-tech sector are far more likely to be engaged in internationalization activity than are service firms, regardless of whether the latter are high-tech. Locational conditions and cooperation activities are generally less important for internationalization of service firms, too, compared to their manufacturing counterparts.
Keywords: M16; M20; L25; R30; O30; 330; Internationalization; service; manufacturing; bivariate probit model; Multinationales Unternehmen; Verarbeitendes Gewerbe; Dienstleistungssektor; Exportindustrie; Schätzung; Neue Bundesländer